Gall bladder wall thickness and C-reactive protein as a predictor of difficult laparoscopic cholecystectomy - Nair A; Appukuttan A; Mathew J; Oommen AN; Joseph A (Journal of Medical and Scientific Research)
ver the past two decades, laparoscopic cholecystectomy has become the preferred method for treating gallstone disease. Despite its many benefits, it is not without potential complications. Accurately predicting the complexity of the surgery remains a challenge. Currently, the duration of a patient’s symptoms is the main criterion for assessing surgical risk. In this study, we hypothesized that increased gallbladder wall thickness and elevated preoperative C-reactive protein (CRP) levels, which are objective markers of inflammation or fibrosis, would be linked to increased difficulty in laparoscopic cholecystectomy. The study spanned 18 months and included 50 patients who met specific inclusion criteria, all of whom underwent either early or interval laparoscopic cholecystectomy. Preoperative ultrasound and CRP values were evaluated, and surgical difficulty was measured using a scoring system. ROC curve analysis was employed to assess CRP as a predictor of difficult laparoscopic cholecystectomy. Intraoperative difficulty was assessed using the Nassar scale. Of the 50 patients, 22 (44%) had grade 1 difficulty, 18 (36%) had grade 2 difficulty, 8 (16%) had grade 3 difficulty, and 2 (4%) had grade 4 difficulty. The chi-square test for the association between gallbladder wall thickness and the difficulty of laparoscopic cholecystectomy revealed a highly significant p-value of <0.001, with a Pearson chi-square statistic of 12.5. ROC analysis indicated that CRP is a reliable predictor of surgical difficulty, with an AUC of 0.790 (95% CI, 0.606-0.974). These findings emphasize the importance of preoperative evaluation of GBWT and CRP, as they can help anticipate surgical challenges, improve planning, and enhance patient outcomes.